Examining Smallholder Farmers’ Needs for Irrigated Crop Production: Insights from South Tongu District, Ghana - Tamekloe, Michael Kossivi; Abiemo, Edem Jerome; Niangue, Josephine Andrea (International Journal of Environmental Sciences, 2025)
Purpose: Research indicates that having irrigation water sources near farms can reduce infrastructure costs, improve farmers’ productivity and income, and foster rural development. On average, farmers cultivate three plots in different areas due to land availability, affordability, and proximity to these water sources. However, in the South Tongu District, farms in water catchment areas are located upstream, which makes accessing irrigation water difficult. Attempting to draw water from a neighbor’s farm can lead to conflicts. Given these challenges, it is essential to examine the needs of farmers and their access to irrigation resources. This paper examines smallholder farmers’ needs for irrigated crop production in the South Tongu District of Ghana. Methodology: A structured questionnaire survey was randomly administered among 120 smallholder farmers from April to May 2023 in six purposively sampled potential irrigation communities. The survey questions focused on farmers’ needs and access to irrigation water sources. Our study is further rooted in utility maximization and risk aversion theories to understand farmers’ choices with lower uncertainty, potential losses, and the option that provides them with the greatest satisfaction. The data were analyzed using SPSS and Excel. Findings: We found that the district has fertile arable lands and abundant water sources. However, farmers expressed concern that farms are not close enough to these water sources, making it difficult to irrigate their crops. Almost all responding farmers (98%) were located far from available streams and the spillage from the Avu Lagoon (75%). About 67% said the Lower Volta River was not near their farm. Another 57% found that the Tordzi River was not nearby, and they cannot afford the cost of irrigation installation. Even those farms near water sources relied on rainfall (78%), indicating the need for infrastructure support. Responding farmers indicated a strong need for credit support to invest in irrigation technologies. About 74% requested canal development, while 71% sought support for irrigation equipment. Additionally, 64% needed technical support, and 54% requested general extension assistance for irrigation practices. Unique Contribution to Theory, Practice, and Policy: This study contributes to making farmers rational and cautious actors towards resource allocation for improved irrigation benefits. The findings will help policy to tailor interventions based on farmers’ socio-economic growth and psychological realities. Moreover, the findings will contribute to the development of policies and support systems to improve farmers’ satisfaction with irrigation practices.